The Impact of the Digital Home Environment on Kindergartners’ Language and Early Literacy - Segers, Eliane; Kleemans, Tijs (Frontiers in Psychology, 2020)
We examined whether a digital home literacy environment could be distinguished from a (traditional) analog home literacy environment, and whether both were related to kindergartners’ language and literacy levels, taking parental expectations into account. Caregivers of 71 kindergarteners filled out a questionnaire on the home environment (expectations, activities, materials), and the children were assessed on language (vocabulary, grammar) and literacy (begin phoneme awareness, segmentation skill, grapheme knowledge) skills. Results showed that a digital environment could be distinguished from an analog environment. However, only the analog environment was related to children’s language abilities. Parental expectations were related directly to both language and literacy abilities. The fact that there was no relation between the digital home environment and language and literacy outcomes might indicate large variation in the quality of the digital home environment. More attention is needed to this part of daily life when growing up in a digital society.